2010
DOI: 10.1016/j.rmed.2010.03.028
|View full text |Cite
|
Sign up to set email alerts
|

Can an evidence-based guideline reminder card improve asthma management in the emergency department?

Abstract: After the implementation of an evidence-based guideline reminder card, medication treatment for acute asthma in the ED was significantly improved; however, asthma education and discharge planning remained unchanged. Future efforts on promoting guideline-based practice in the ED should focus on these components.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…They also have recently been shown to improve compliance with evidence-based guidelines for asthma management (10). However, few studies have examined the role of pocket-cards in changing inpatient analgesic prescribing practices for children.…”
Section: Introductionmentioning
confidence: 99%
“…They also have recently been shown to improve compliance with evidence-based guidelines for asthma management (10). However, few studies have examined the role of pocket-cards in changing inpatient analgesic prescribing practices for children.…”
Section: Introductionmentioning
confidence: 99%
“…However, despite the availability of clinical practice guidelines and efficacious treatment options, [9][10][11][12][13][14] asthma is not well controlled for many patients, 15 and poorer asthma control is associated with higher costs and increased resource use. [15][16][17][18] In addition, large gaps still exist between the care recommended by guidelines and that actually provided, [19][20][21][22][23][24][25][26][27][28] and there is an inadequate focus on self-management. 29 A study from the Rand Corporation published in 2007 showed that adherence to 17 recommended ambulatory care indicators for children with asthma was only 46%.…”
mentioning
confidence: 99%
“…Studies have suggested lack of familiarity and lack of awareness of CPG as potential barriers to their use . Initiatives to improve systematic implementation of CPG, such as a system to monitor adherence to guidelines, use of opinion leaders to promote CPG use and reminder cards or evidence‐based asthma management protocols at the point of care, may improve adherence . In conclusion, the findings of this study provide comprehensive baseline assessment of paediatric asthma care across the entire patient journey (i.e.…”
Section: Discussionmentioning
confidence: 88%